Same‐day discharge in selected patients undergoing atrial fibrillation ablation. Issue 11 (13th October 2019) - Bartoletti, Stefano; Mann, Mandeep; Gupta, Akanksha; Khan, Abdul Muhaymin; Sahni, Ankita; El‐Kadri, Moutaz; Modi, Simon; Waktare, Johan; Mahida, Saagar; Hall, Mark; Snowdon, Richard; Todd, Derick; et al.
Abstract: Background: Atrial fibrillation (AF) ablation is a complex procedure, generally requiring at least one overnight hospital stay. We investigated the safety and feasibility of early mobilization and same‐day discharge following streamlined peri‐ablation management for AF. Methods: From 2014, we offered same‐day discharge to selected patients who underwent uncomplicated AF ablation on the morning lists, with ultrasound‐guided femoral access, uninterrupted warfarin or minimal interruption in novel oral anticoagulants, and reversal of intraprocedural heparin with protamine. Patients were discharged 6‐8 h postprocedure and offered access to a dedicated nurse helpline. Results: Of 1599 AF ablation cases performed from April 2014 to March 2017, 811 (50.7%) were performed on the morning lists and 169/811 (20.8%) were discharged on the same day. Excluding 26 research cases, 1/143 (0.7%) had transient right phrenic nerve palsy and five (3.5%) cases experienced minor problems that did not preclude same‐day discharge; three (2.1%) needed rehospitalization postdischarge: one for pericarditic chest pain and two for nausea/vomiting. Compared to 642 overnight cases, day‐case procedures were shorter, more likely to be redos, to be performed under sedation rather than general anesthesia, and less likely to involve linear lesions and electrical cardioversion. There were no significant differences in patient age, gender, body mass index, CHA2 DS2 ‐VASc, in preprocedural anticoagulation regimen (warfarin vs novel anticoagulants vs no anticoagulation) and in choice of ablation method (cryoballoon vs radiofrequency). Conclusions: Selective same‐day discharge after AF ablation is safe and feasible using a streamlined peri‐procedural care protocol. Wider adoption can potentially reduce health‐care costs while improving patient experience.